Feeding habits, recruitment and status of sergestid shrimps (Acetes intermedius omori) stock in Bintulu, Sarawak - Saini, Masitah (2013)
Growth, mortality, feeding habits, recruitment and status of the stock of Acetes intermedius, whom locally known as ‘udang geragau’, from the coastal waters of Bintulu, Sarawak (N 03˚ 20’ 12” and E 113˚ 02’ 01”) were examined during February 2009 to December 2010. The study conducted using push net or known locally as Sungkor, as mentioned by Omori (1975). It is a triangular shape net with dimensions between 5-6m in length, 4.0-4.5m in wide, and 3.0-3.5m in height. The mean mesh sizes were 3.2±0.27 cm at the anterior section, 0.75±0.0 cm at the middle and 0.5±0.008 at cod end if stretched. Approximately, two kilograms of Acetes samples were taken for each month. The samples were fixed in 70% alcohol at the collection site before transported to UPM Serdang, Selangor. Upon arrival, the samples were rinsed with tap water for twenty minutes before fixed in 10% formalin and analyzed after 2-3 days of preservation. According to simple resultant index (%SRI), the highest percentage of food items was zooplankton (28.13%) followed by plant matter (13.72%), unidentified item (13.19%), sand and mud (13.01%), debris (11.79%), phytoplankton (10.91%) and algae (9.26%). The various composition of food items proved that A. intermedius is an omnivore. A. intermedius can switch their major food preference depends on the abundant types of food available and food competition between marine animals. The growth, mortality, recruitment and relative yield per recruit of A. intermedius were investigated based on monthly length-frequency data, using FiSAT software. The average natural mortality (2.21 yr-1) was higher than the average value of fishing mortality (1.73 yr-1) indicates the imbalance position in the stock. The average value for exploitation level (E) was 0.43. This indicates that the fishery of A. intermedius in the coastal waters of Bintulu is under exploited. This is based on the assumption that a stock is optimally exploited when fishing mortality (F) equals natural mortality (M), or E = (F/Z) = 0.5. The annual recruitment of A. intermedius showed continuous recruitment with two major peaks in April to May and August to September (2009) and March to April and August to September (2010). This indicates that there are two major cohorts produced per year. The peaks were affected by environmental factors and the availability of food source. Although the fishery of A. intermedius is under exploited, precautionary measures should be taken in order to maintain the stock balance of A. intermedius in Bintulu coastal waters.